The Battle for Okinawa - Yahara, Hiromichi (Colonel) 1902-1981 (New York Jhon Wiley & Sons, 1995)
Yahara was Senior Staff Officer of the 32nd Army, and the highest ranking Japanese officer to leave Okinawa alive.
Include Pictures and Index
Keywords: World War (1939-1945) -- Japan--Okinawa Island